Analytical Performance of Four Polymerase Chain Reaction (PCR) and Real Time PCR (qPCR) Assays for the Detection of Six Leishmania Species DNA in Colombia - León, Cielo M.; Muñoz, Marina; Hernández, Carolina; Ayala, Martha S.; Flórez, Carolina; Teherán, Aníbal; Cubides, Juan R.; Ramírez, Juan D. (Frontiers in Microbiology, 2017)
Leishmaniasis comprises a spectrum of parasitic diseases caused by protozoans of the genus Leishmania. Molecular tools have been widely employed for the detection of Leishmania due to its high sensitivity and specificity. However, the analytical performance of molecular platforms as PCR and real time PCR (qPCR) including a wide variety of molecular markers has never been evaluated. Herein, the aim was to evaluate the analytical performance of 4 PCR-based assays (designed on 4 different targets) and applied on conventional and real-time PCR platforms. We evaluated the analytical performance of conventional PCR and real time PCR, determining exclusivity and inclusivity, Anticipated Reportable Range (RRA), limit of detection (LoD) and accuracy using primers directed to kDNA, HSP70, 18S and ITS-1 targets. It was observed that the kDNA was the most sensitive but does not meet the criterion of exclusivity. The HSP70 presented a higher limit of detection in conventional PCR and qPCR in comparison with the other markers (1x101 and 1x10- 1 equivalent parasites/mL respectively) and had a higher coefficient of variation in qPCR. No statistically significant differences were found between the days of the test with the 4 molecular markers. The present study revealed that the 18S marker presented the best performance in terms of analytical sensitivity and specificity for the qPCR in the species tested (species circulating in Colombia). Therefore, we recommend to explore the analytical and diagnostic performance in future studies using a broader number of species across America.